To evaluate the expression when x = -3, and y = -1, we need to substitute these values into the expression, solve the resulting operations, and simplify if necessary. Then, we have:
![-x^2-3xy+5y^3,x=-3,y=-1](https://img.qammunity.org/2023/formulas/mathematics/college/w4kb5sb9ihvwpylknrpq1npgrn3aldb2tk.png)
Then, we have:
![-(-3)^2-3(-3)(-1)+5(-1)^3=-9-3(3)+5(-1)=-9-9-5=-23](https://img.qammunity.org/2023/formulas/mathematics/college/xiade45f2aieoxyoxv3j6kom1ujppfi8t0.png)
Therefore, the value for the evaluated expression when x = -3, and y = -1 is equal to -23.